Faktor-Faktor Yang Mempengaruhi Perilaku Impulsive Buying Pada Platform E-Commerce Shopee - Rachmad Sholeh; Khasbulloh Huda (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
The shopping behavior of customers worldwide has changed from offline shopping to online shopping thanks to technological advances. This research aims to determine the influence of discounts, ranting, and online customer reviews on impulsive buying, both partially and simultaneously, and determine which variables have the most significant impact. This research uses quantitative research, using a Population of students at Mayjen Sungkono University, Mojokerto, Faculty of Economics, semester 3. This research uses multiple linear regression with the t-test and F-test to see the hypothesis results. The results of this study show that partially the variables of discount, branch and online customer review on impulsive buying have a positive and significant influence in this case can be proven by the test results at the P-value <0.001 for discount, 0.002 for branch and online customer review of <0.001 which has a value of <0.005, and for simultaneous testing also has a positive and significant influence as evidenced by the results of the P-Value of <0.001 which is smaller than 0.005. While the value of the influence on each discount variable is 0.367, the branch variable is 0.268, and the online customer review variable is 0.372. from these results the variable that has the greatest influence is the online customer review variable.